2021
DOI: 10.1111/ped.14506
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sclerotherapy with polidocanol in children with internal hemorrhoids

Abstract: Background Hemorrhoids are an extremely rare condition in children, and data on its incidence and treatment in the pediatric population remains scarce. We retrospectively reviewed children who underwent sclerotherapy for internal hemorrhoids, and analyzed patients' characteristics and outcomes. Methods A total of 14 pediatric patients who underwent sclerotherapy were included. Patients' ages and the required amount of polidocanol, depending on the grade of hemorrhoids, and the correlation between age and volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Polidocanol is a commonly used injection sclerotherapy that has been widely used for injection sclerotherapy of internal hemorrhoids[ 14 , 15 ]. Polidocanol is injected into the anus mirror or via colorectal colonoscopy under direct intravascular injection of pathological changes and causes minimal damage to the mucous membrane tube and anal cushion.…”
Section: Discussionmentioning
confidence: 99%
“…Polidocanol is a commonly used injection sclerotherapy that has been widely used for injection sclerotherapy of internal hemorrhoids[ 14 , 15 ]. Polidocanol is injected into the anus mirror or via colorectal colonoscopy under direct intravascular injection of pathological changes and causes minimal damage to the mucous membrane tube and anal cushion.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure benefits patients with mild to moderate symptoms who do not respond to conservative measures such as dietary changes and topical medications. Sclerotherapy is considered a safe and effective alternative to surgical intervention in these cases and may also be helpful for patients who are unable or unwilling to undergo surgery [39].…”
Section: Sclerotherapymentioning
confidence: 99%
“…The procedure is typically performed on an outpatient basis and may be repeated as necessary to achieve the desired results. Studies have reported varying success rates of sclerotherapy in treating hemorrhoids, depending on the severity of the condition and other factors [39,40]. However, on average, sclerotherapy has been shown to have a success rate of approximately 70-80% in treating first-and second-degree hemorrhoids.…”
Section: Sclerotherapymentioning
confidence: 99%
“…Patients with grade III hemorrhoids required a significantly larger amount of polidocanol than those with grade II. Sclerotherapy with polidocanol was a safe and effective treatment for children with symptomatic hemorrhoids, which was simple to operate with minimal anesthesia and was associated with very low morbidity [ 25 ]. HIV-positive patients should avoid rubber band ligation [ 26 ].…”
Section: Injection Sclerotherapymentioning
confidence: 99%